The Role of the North Sumatra Provincial Bawaslu in the 2019 Election: Performance Analysis and Design of an Adaptive Supervision Model - Lubis, Yurial Arief; Ilham, Muh.; Tahir, M. Irwan; Achmad, Mansyur (Universitas Medan Area, 2025)
This study aims to analyze the role of the North Sumatra Provincial Election Supervisory Agency (Bawaslu) in implementing the 2019 Election and formulate a more effective and contextual supervision model. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, and documentation from informants such as Bawaslu and KPU commissioners, academics, party administrators, and the public. The results of the study show that the role of Bawaslu has not been optimal due to various obstacles, including limited human resources, weak coordination between institutions, and a recruitment process that is not transparent and full of political interests. Election supervision tends to be administrative and formal, with no strict law enforcement measures. For this reason, the researcher offers a supervision model that integrates the role indicators, according to Biddle and Thomas, with the three types of Donnelly supervision and adds two important indicators: the quality and quantity of human resources. This model is expected to strengthen the professionalism and effectiveness of Bawaslu's supervision in overseeing democratic, honest, fair, and integrity elections and increase public trust in the region's election process.